The staining effect of cigarette smoke on different dental materials - Hilal EKSI OZSOY (Journal of Dental Problems and Solutions - Peertechz Publications, 2020)
Among the aesthetic properties of restorative and prosthetic materials used in dentistry, color stability is an important issue. Color changes are examined using many coloring agents such as coffee, tea and mouthwash. One of these coloring agents is cigarette smoke. The rapid increase in the number of cigarette users in the world and the presence of a wide variety of dental materials have made it popular to study the impact among them. The purpose of this mini review is to evaluate the studies examining the staining effects of smoking on dental composite and denture teeth. Some studies have shown that smoking has an effect on dental materials. However, more studies are needed to examine the effect of smoking on the color stability of new dental materials.